2018
DOI: 10.1371/journal.pone.0196053
|View full text |Cite
|
Sign up to set email alerts
|

Six-year positive effects of a mindfulness-based intervention on mindfulness, coping and well-being in medical and psychology students; Results from a randomized controlled trial

Abstract: Longitudinal research investigating the enduring impact of mindfulness training is scarce. This study investigates the six-year effects of a seven-week mindfulness-based course, by studying intervention effects in the trajectory of dispositional mindfulness and coping skills, and the association between those change trajectories and subjective well-being at six-year follow-up. 288 Norwegian medical and psychology students participated in a randomized controlled trial. 144 received a 15-hour mindfulness course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
96
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 60 publications
10
96
0
7
Order By: Relevance
“…This outcome may be due to low adherence by the nurses taking part in the studies, since regular training is known to maintain low levels of burnout. However, the studies in question (Duarte & Pinto-Gouveia, 2016;Wong, Teng, Chee, Doshi, & Lim, 2018) reported high dropout rates, a pattern that has been repeated in other studies of healthcare workers (De Vibe et al, 2018;Shapiro, Astin, Bishop, & Cordova, 2005). Nevertheless, in line with some of our review findings, other authors have observed persistent improvements, lasting up to 12 months postintervention, with a reduction of 8.2% in burnout scores (Askey-Jones, 2018;Fortney et al, 2013;Lebares et al, 2018;Martín-Asuero & García-Banda, 2010;Steinberg et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This outcome may be due to low adherence by the nurses taking part in the studies, since regular training is known to maintain low levels of burnout. However, the studies in question (Duarte & Pinto-Gouveia, 2016;Wong, Teng, Chee, Doshi, & Lim, 2018) reported high dropout rates, a pattern that has been repeated in other studies of healthcare workers (De Vibe et al, 2018;Shapiro, Astin, Bishop, & Cordova, 2005). Nevertheless, in line with some of our review findings, other authors have observed persistent improvements, lasting up to 12 months postintervention, with a reduction of 8.2% in burnout scores (Askey-Jones, 2018;Fortney et al, 2013;Lebares et al, 2018;Martín-Asuero & García-Banda, 2010;Steinberg et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This result indicates that a high use of PFC increases PWB, while a high use of EFC decreases PWB. Our results are consistent with those of previous studies (De Vibe et al, ; Park & Adler, ; Tavakolizadeh et al, ). The correlationship among PFC, EFC, and PWB is consistent with a recent study (Lee et al, ) in which researchers indicated that approach‐oriented coping similar to PFC was associated with improved PWB, whereas avoidant coping similar to EFC was a counterproductive coping style for PWB.…”
Section: Discussionsupporting
confidence: 94%
“…Stress coping styles have long been studied as mediator variables between stress and PWB (De Vibe et al, ; Malek, Fahrudin, & Kamil, ; Park & Adler, ; Tavakolizadeh, Mohammadi, & Safarzade, ). In Lazarus and Folkman’s () cognitive‐phenomenological model, cognitive appraisal of stress experience and coping strategies play key roles in the relationship between stress and adaptation to it.…”
mentioning
confidence: 99%
“…To improve nursing students’ psychological well‐being, their cognitive distortions and depression level should be determined, and for students at risk, mindfulness‐based intervention should be implemented in nurse education settings. Because mindfulness‐based intervention increased coping and well‐being in medical and psychology students . According to, mindfulness meditation programs had a positive impact on nursing students' stress, anxiety, depression, burnout, sense of well‐being and empathy.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…Because mindfulness-based intervention increased coping and well-being in medical and psychology students. 44 According to, 45 mindfulness meditation programs had a positive impact on nursing students' stress, anxiety, depression, burnout, sense of well-being and empathy.…”
Section: Implications For Nursingmentioning
confidence: 99%